Atlas físico-ambiental como ferramenta de subsídio à gestão da bacia hidrográfica do rio Uaicurapá, Parintins - AM - Brasil - Fernandes, Andrei Tavares (2020)
The context of Water Resources Management, in which river basins are legally established as a management and planning unit, can be associated with technological advances, such as current forms of storage, dissemination and availability of information, in this case, those of whose technical-scientific. Given this context and meeting the lack of mapping in sub-basins of the Amazon River and the availability of data involving Geographic Information Systems (GIS), this work aimed to prepare the Physical-Environmental Atlas, in digital format, from the Uaicurapá River Hydrographic Basin (BHRU), on the border of the state of Amazonas and Pará, as a subsidy tool for the management of water resources. The work involved applied qualitative and quantitative research, supported by the use of Thematic Cartography, Remote Sensing, Geoprocessing and field survey methods and procedures. As a result, the BHRU Physical-Environmental Atlas was prepared, comprising 13 maps with the themes: The location of the Uaicurapá River, Hydrography, BHRU Subdivisions, The Upper Course, The Middle Course, The Low Course, The Relief, The Slope, Soil Types, Land Use and Coverage, Precipitation (Rain), Deforestation and Environmental Vulnerability, in addition to elements such as graphics and photographs. The material also presents the estimated area of the BHRU with 1 760 km2, length of the main river in 84 km, location of the source, definition of the mouth, definition of the hierarchical position of the sub-basin in relation to the hydrographic basin of the Mamuru River (BHRM) and its interstate aspect. This last aspect presents itself as a challenging opportunity for the shared management of water resources, between the states of Amazonas and Pará, and the Union, in order to further integrate them with the strengthening of the National Water Resources Management System, the SINGREH. Keyword: Atlas. Geoprocessing. Water resources.